Hippocampal-neocortical interactions sharpen over time for predictive actions - Nicholas C. Hindy (Nature Portfolio, 2019)
In familiar environments, humans automatically anticipate the sensory consequences of their motor actions. Here, the authors show how action-based predictions arise from interactions between the hippocampus and visual cortex, and how these interactions strengthen and weaken over time.